Site-Specific Delivery of Doxorubicin Using Cell-Penetrating Peptide for Lung Cancer Chemotherapy - Gautam, Laxmikant; Vyas, Suresh P. (International Journal of Pharmaceutical Investigation)
Recent studies have focused heavily on tumor-oriented nanocarriers mediated by cell- penetrating peptides (CPPs). However, the loss of CPPs in normal tissues and enzymatic degradation in circulation frequently prevented the use of CPPs in vivo. To alleviate these limitations, CPPs needed to be kept immobilized before they arrived at the intended target for receptor-mediated endocytosis (RME). In this study, we developed CAR/DOX-Liposomes with doxorubicin hydrochloride (DOX) entrapped in the hydrophilic core of liposomes using a thin film hydration method, and CAR peptide was subsequently conjugated through SPDP chemistry on the surface of liposomes as targeting moiety to develop and improved targeted cancer chemotherapy. The prepared liposomes were characterized and evaluated for different parameters which were recorded to be vesicle size 275.2±5.65 nm, polydispersity index 0.260±0.85, Zeta-potential -33.90±2.42 mV, and % entrapment efficiency 83.96±2.56 %. In addition, Transmission electron microscopy (TEM), and Atomic Force Microscopy (AFM) studies were conducted to assess morphology and in vitro drug release performed. Further, the Cell line study of the CAR/DOX-Liposomes was studied over the lung cancer cell line HOP-62 and the comparison IC50 values were determined. The study establishes that CAR/DOX-Liposomes offer specific delivery of DOX to the heparan sulfate receptor(s) exclusively overexpressed on the cancer cells.
Keywords: Lung Cancer; DOX; Heparan sulfate; CAR peptide.